1975
DOI: 10.1002/tera.1420110110
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenesis in cats associated with griseofulvin therapy

Abstract: Multiple congenital malformations occurred in kittens of three cats treated orally at weekly intervals with 500-1000 mg of the antifungal drug griseofulin. Malformations of the brain included exencephaly, malformed prosencephalon, caudal displacement, and hydrocephalus. Skeletal malformations included cranium bifidium, spina bifida (C1 through C4, and sacral), abnormal atlantooccipital articulation, cleft palate, absence of maxillae, and lack of tail vertebrae. Cyclopia and anophthalmia with absence of optic n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

1978
1978
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 4 publications
0
32
0
2
Order By: Relevance
“…15,16 A hereditary predisposition has been shown in Burmese cats, 16 but teratogenic factors and nutritional deficiencies may play a role in the development of such malformations. 17,18 Based on the small number of cases collected throughout Europe in this study, it appears to be a sporadically occurring disease, that might be underdiagnosed because diagnosis requires advanced imaging and some dogs may not have any neurologic signs, as occurred in the dog diagnosed with lymphoma and an incidental MEC. Early head trauma could be a predisposing factor, as occurred in at least 1 of the cases.…”
Section: Discussionmentioning
confidence: 95%
“…15,16 A hereditary predisposition has been shown in Burmese cats, 16 but teratogenic factors and nutritional deficiencies may play a role in the development of such malformations. 17,18 Based on the small number of cases collected throughout Europe in this study, it appears to be a sporadically occurring disease, that might be underdiagnosed because diagnosis requires advanced imaging and some dogs may not have any neurologic signs, as occurred in the dog diagnosed with lymphoma and an incidental MEC. Early head trauma could be a predisposing factor, as occurred in at least 1 of the cases.…”
Section: Discussionmentioning
confidence: 95%
“…Effects attributed to griseofulvin administration during pregnancy have been reported in several animal species (3,5,8,11,14,16,17,18). Lesions in the offspring mainly consist of skeletal abnormalities (3,8), craniofacial anomalies including palatoschisis (3,8,11,14), microphthalmia/anophthalmia (5,8,14,16), cyclopia (14), and abscence of eyelids (18).…”
Section: Discussionmentioning
confidence: 95%
“…Because of the placental transfer of the drug (13) and its potential effect on mitosis in mammalian cells, administration of griseofulvin during pregnancy is strongly disadvised (2). Teratogenic effects attributed to griseofulvin administration have been reported in humans (4,12), laboratory animals (8,16,17), dogs (11), and cats (3,5,14,18). Although Einstein et al (2) state that griseofulvin also is teratogenic in horses, no original reports confirming this statement could be found in veterinary databases (VETCAB; FOCUS).…”
Section: Introductionmentioning
confidence: 99%
“…9 An example of routine use in veterinary medicine is griseofulvin, an antifungal drug for animals with dermatomycosis. Scott et al (1975) observed multiple congenital defects in newborn cats whose mothers orally received high doses of griseofulvin (500-1000 mg, at weekly intervals). There were cerebral defects, skeletal defects, cleft palate, anophthalmia with absence of optic nerves, anal atresia, lack of atrioventricular valves and other defects.…”
Section: Genetic Etiologymentioning
confidence: 99%